Global Perspectives on Immunization During Pregnancy and Priorities for Future Research and Development: An International Consensus Statement - Abu-Raya, Bahaa; Maertens, Kirsten; Edwards, Kathryn M.; Omer, Saad B.; Englund, Janet A.; Flanagan, Katie L.; Snape, Matthew D.; Amirthalingam, Gayatri; Leuridan, Elke; Damme, Pierre Van; Papaevangelou, Vana; Launay, Odile; et al. (Frontiers in Immunology, 2020)
Immunization during pregnancy has been recommended in an increasing number of countries. The aim of this strategy is to protect pregnant women and infants from severe infectious disease, morbidity and mortality and is currently limited to tetanus, inactivated influenza, and pertussis-containing vaccines. There have been recent advancements in the development of vaccines designed primarily for use in pregnant women (respiratory syncytial virus and group B Streptococcus vaccines). Although there is increasing evidence to support vaccination in pregnancy, important gaps in knowledge still exist and need to be addressed by future studies. This collaborative consensus paper provides a review of the current literature on immunization during pregnancy and highlights the gaps in knowledge and a consensus of priorities for future research initiatives, in order to optimize protection for both the mother and the infant.